Comparative Analysis of Compact Satellite Polarizers Based on a Guide with Diaphragms - Piltyay, S.; Bulashenko, A.; Fesyuk, I.; Bulashenko, O. (Advanced electromagnetics, 2021)
In this article we carry out the comparative analysis of new compact satellite polarisers based on a square guide with diaphragms. The main electromagnetic parameters of the developed microwave guide devices with various amount of diaphragms were obtained within the satellite frequency interval from 10.7 GHz to 12.75 GHz. Waveguide polarization converters with different amount of diaphragms from 2 to 5 have been designed and optimized. The main parameters of the presented polarizer were calculated applying the numerical method of finite integration in the frequency domain. Optimization of the electromagnetic parameters of the developed waveguide devices was carried out using the software CST Microwave Studio. As a result, sizes of the device designs have been optimized for the provision of improved polarization and phase parameters. The performed analysis showed that a waveguide polarizer with five diaphragms has the best electromagnetic parameters. The developed compact polarizer with five diaphragms based on a square guide provides a minimum deviation of the output phase difference from 90 degrees and high level of isolation between linear polarization over the entire operating frequency range. Presented in the article compact waveguide polarization converters can be applied in satellite systems, which require efficient polarization separation of signals.